Institutions and Development in MENA Region: Evidence from the Manufacturing Sector - Mahmoud Arayssi; Ali Fakih (Institute for the Study of Labor (IZA), 2015)
This paper examines the role of institutions (including civil law origin), financial deepening and degree of regime authority on growth rates in the Middle East and North Africa (MENA) region using panel data through a fixed effect model. The results reveal that English civil law origin and the establishment of the rule of law work with the development of financial institutions to increase economic growth in these economies; however, the democratization of the political institutions and foreign direct investment do not assist financial development in promoting economic growth. The findings emphasize the prominence of overcoming institutional weaknesses and establishing transparent public policy governing businesses as a pre-requisite for successful universal integration in developing countries.
Keywords: G2; O16; P48; 330; economic growth; institutional development; financial development; MENA region